Translating life : studies in transpositional aesthetics - Chew, Shirley; Stead, Alistair (Liverpool English texts and studies ;, 1999)
This volume brings together eighteen substantial essays by distinguished scholars, critics and translators, and two interviews with eminent figures of British theatre, to explore the idea and practice of translation. The individual, but conceptually related, contributions examine topics from the Renaissance to the present in the context of apt exploration of the translation process, invoking both restricted and extended senses of translation. The endeavour is to study in detail the theory, workings and implications of what might be called the art of creative transposition, effective at the lev.